Remodelamento vascular em camundongos ateroscleróticos na coexistência de hipertensão renovascular 2R1C - Nogueira, Breno Valentim (2005)
ApoE-/- knockout mouse is a model for studies of hypercholesterolemia, which is characterized by developing atherosclerotic lesions mainly in great arterial vessels such as the aortic arch, which is a site of baroreceptor nerve endings. In addition, it is known that angiotensin affects the atherosclerotic process and baroreflex sensitivity. Thus, the aim of this study was to evaluate morphological changes in the aortic arch in ApoE-/- mice with renovascular hypertension. Male (12-14 weeks old) C57 and ApoE-/- mice received a clip (0.12mm) on the renal artery to induce renovascular hypertension (C57-HT, N=11; ApoE-HT, N=11) and were compared with age-matched sham mice (C57-Sham, N=11; ApoE-Sham, N=11). After 28 days, mean arterial pressure (MAP) measured in conscious animals was higher in C57-HT and ApoE-HT (128±3 and 126±3 mmHg) than in their respective controls (103±2 and 104±2 mmHg, p<0.05). The animals were euthanized and perfused with a fixative solution at pressure equal to the MAP observed in each animal. The cross section area of the aortic arch was greater in C57-HT and ApoE-HT (0.76±0.05 and 0.73±0.03 mm2) than in their respective controls (0.64±0.02 and 0.63±0.03 mm2, p<0.05). The wall vessel area was also greater in these hypertensive groups (0.18±0.01 and 0.19±0.01 mm2) than in the normotensive groups (0.15±0.01 and 0.17±0.01 mm2, p<0.05). Consequently, the lumen vessel area followed the same results. In conclusion, our data indicate that at least at the early stage of atherosclerosis the remodeling process is not yet observed in the ApoE-/- mouse. Renovascular hypertension by itself leads to a positive remodeling of the aortic arch, which is aggravated by the association with atherosclerosis when compared with the C57 control.